2015
DOI: 10.3233/bpl-150019
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5/Irisin – Their Role in the Nervous System and as a Mediator for Beneficial Effects of Exercise on the Brain

Abstract: Exercise can improve cognitive function and the outcome of neurodegenerative diseases, like Alzheimer’s disease. This effect has been linked to the increased expression of brain-derived neurotrophic factor (BDNF). However, the underlying molecular mechanisms driving the elevation of this neurotrophin remain unknown. Recently, we have reported a PGC-1α-FNDC5/irisin pathway, which is activated by exercise in the hippocampus in mice and induces a neuroprotective gene program, including Bdnf. This review will focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 58 publications
4
63
0
2
Order By: Relevance
“…In addition, Lourenco et al have recently demonstrated that peripheral overexpression of FNDC5/irisin rescues memory impairment, whereas blockade of peripheral FNDC5/irisin attenuates the neuroprotective actions of physical exercise on synaptic plasticity and memory in an Alzheimer mice model. These data indicate that either irisin itself can cross the blood–brain barrier to induce brain effects or that irisin may induce another peripheral unknown factor with such a property …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, Lourenco et al have recently demonstrated that peripheral overexpression of FNDC5/irisin rescues memory impairment, whereas blockade of peripheral FNDC5/irisin attenuates the neuroprotective actions of physical exercise on synaptic plasticity and memory in an Alzheimer mice model. These data indicate that either irisin itself can cross the blood–brain barrier to induce brain effects or that irisin may induce another peripheral unknown factor with such a property …”
Section: Discussionmentioning
confidence: 86%
“…For all these reasons, irisin is considered a critical myokine related to body metabolism. Moreover, increasing evidence proposes irisin also as a mediator of the beneficial effects of exercise on the brain function (memory) and in neurodegenerative diseases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kempermann (2008) suggests that novelty and exploration may be key elements of these combined physical and cognitive challenges. Recent work provides a clue as to how movement triggers production of neurotrophins critical for neuroplasticity [64]. In rodent models, exercising muscles produce myokines, including FNDC5 and cathepsin B, which regulate metabolic processes and may improve muscle function while also inducing increased levels of BDNF [6466].…”
Section: The Adaptive Capacity Modelmentioning
confidence: 99%
“…Indeed, overexpression of peroxisome proliferator-activated receptor-gamma co-activator (PGC-1α) in muscle increased production of Fibronectin type III domain containing 5 (FNDC5), which is cleaved and secreted as irisin, increasing hippocampal Bdnf expression. Exercise elevates irisin in human plasma (Wrann, 2015). Furthermore, PGC-1α1 overexpression in muscle has an antidepressant-like effect by reducing entry of neurotoxic kynurenine into the brain (Agudelo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%